Study on the Near-Distance Object-Following Performance of a 4WD Crop Transport Robot: Application of 2D LiDAR and Particle Filter - Eun-Seong Pak; Byeong-Hun Kim; Kil-Soo Lee; Yong-Chul Cha; Hwa-Young Kim (Applied Sciences)
In this paper, the development and performance evaluation of a 4WD robot system designed to follow near-distance moving objects using a 2D LiDAR sensor are presented. The study incorporates identifier (ID) classification and a distance-based dynamic angle of perception model to enhance the tracking capabilities of the 2D LiDAR sensor. A particle filter algorithm was utilized to verify the accuracy of object tracking. Furthermore, a proportional–derivative (PD) controller was designed and implemented to ensure the stability of the robot during operation. The experimental results demonstrate the potential applicability of these approaches in various industrial applications.